The Effectiveness of Psychological Dhikr Therapy in Improving the Quality of Life of Cancer Patients Undergoing Chemotherapy - Syahri, Alfi; Marlina, Siti; Rosaulina, Meta; Manik, Maria Hermita; Harigustian, Yayang; Pasambo, Yourisna; Putra, Komang Ardidhana Nugraha (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2024)
Introduction: Cancer is a chronic disease with increasing prevalence globally, including in Indonesia, and has a significant impact on patients' quality of life. This impact includes not only physical, but also emotional and spiritual aspects, especially for patients undergoing chemotherapy, who often face physical side effects such as fatigue, pain, and psychological disorders such as anxiety and depression. Objective: This study aims to analyze the effectiveness of dhikr therapy in improving the quality of life of cancer patients during chemotherapy. Methods: The study used a quasi-experimental approach with a one-group pre-post test design. The sample consisted of 37 adult cancer patients undergoing chemotherapy at Sembiring General Hospital, selected by purposive sampling technique. Dhikr intervention was conducted for 4 weeks, with data collected using the WHOQOL-BREF questionnaire to measure quality of life, as well as dhikr activity logs. Data analysis used paired t-test to evaluate changes before and after the intervention. Results: This study showed a significant improvement in patients' quality of life after dhikr therapy. The mean change score reached -9.184 with a standard deviation of 4.373, and a p-value of 0.000 (p < 0.05), indicating that this difference was statistically significant. Conclusion: Dhikr therapy is effective in improving the quality of life of cancer patients, especially in the physical, emotional, and spiritual dimensions.